2020
DOI: 10.2355/isijinternational.isijint-2019-246
|View full text |Cite
|
Sign up to set email alerts
|

Melting Behaviour of Iron Ore Pellet Bed under Nut Coke Mixed Charge Conditions

Abstract: The melting and dripping behaviour of an iron ore pellet bed mixed with nut coke are investigated through a series of quenching, melting and dripping experiments. In the melting bed of iron ore pellets, nut coke acts as a frame to maintain the passage for the gas flow. The iron carburisation level of the pellet shell is found to control the melting temperature of the pellet bed. Simultaneous and layer-wise melting is observed for the pellet bed with and without mixed nut coke, respectively. In the case of pell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Fossil-based nut coke was used as a reference material in the reactivity experiments, which was provided by SSAB, Raahe. Nut coke is a term used for metallurgical coke that is typically in the size range of 8-40 mm in diameter [15].…”
Section: Methodsmentioning
confidence: 99%
“…Fossil-based nut coke was used as a reference material in the reactivity experiments, which was provided by SSAB, Raahe. Nut coke is a term used for metallurgical coke that is typically in the size range of 8-40 mm in diameter [15].…”
Section: Methodsmentioning
confidence: 99%
“…Gavel et al reported that the carburization of solid iron with solid carbon is superior to that with CO gas. [3][4][5] There are several steps in the melting reaction of iron with solid carbon: a) melting reaction of iron, b) carbon diffusion in solid iron, c) mass transfer in liquid Fe-C alloy and d) dissolution of graphite into liquid Fe-C alloy. Some researchers have reported the In-situ observation behavior of carburization and melting of iron.…”
Section: Effect Of Silica In Ash Of Coke On Carburization and Melting Of Ironmentioning
confidence: 99%
“…The iron present as the pellet shell carburises first by its direct contact with the coke to melt later. This continues to cause the layer-wise melting and dripping of the pellet bed [19,25].…”
Section: Quenched Pellet Bedmentioning
confidence: 99%